Impact of supervision of methadone consumption on deaths related to methadone overdose (1993-2008): analyses using OD4 index in England and Scotland. (16th September 2010) - Strang, John; Hall, Wayne; Hickman, Matt; Bird, Sheila M
Abstract : Objective To evaluate the impact of introduction of supervision of methadone dosing on deaths related to overdose of methadone in Scotland and England between 1993 and 2008 while controlling for increased prescribing of methadone. Design Analysis of annual trends in deaths related to overdose of methadone in relation to defined daily doses of methadone prescribed. Setting Scotland and England. Population Deaths in which methadone was coded as the only drug involved or as one of the drugs implicated. Main outcome measure Annual OD4-methadone index (number of deaths with methadone implicated per million defined daily doses of methadone prescribed in that year). Results OD4-methadone declined substantially over the four epochs of four years between 1993 and 2008. It decreased significantly (P<0.05) in 10 of 12 epoch changes: in Scotland from 19.3 (95% confidence interval 15 to 24) to 4.1 (2.8 to 5.4) and finally to 3.0 (2.4 to 3.5) for methadone only deaths (and from 58 to 29 to 14 for deaths with any mention of methadone); in England from 27.1 (25 to 29) to 24.8 (23 to 27) and finally to 5.8 (5.3 to 6.3) for methadone only deaths (and from 46 to 42 to 12 for deaths with any mention of methadone). The decreases in OD4-methadone were closely related to the introduction of supervised dosing of methadone in both countries, first in Scotland (1995-2000) and later in England (1999-2005). These declines occurred over periods of substantial increases in prescribing of methadone (18-fold increase in defined daily doses per million population annually in Scotland and sevenfold increase in England). Conclusions Introduction of supervised methadone dosing was followed by substantial declines in deaths related to overdose of methadone in both Scotland and England. OD4-methadone index analyses, controlled for substantial increases in methadone prescribing in both countries, identified at least a fourfold reduction in deaths due to methadone related overdose per defined daily dose (OD4-methadone) over this period.